2017
DOI: 10.7554/elife.24106
|View full text |Cite
|
Sign up to set email alerts
|

All about the RNA after all

Abstract: RNA molecules cause the proteins involved in the formation of germ granules to coalesce into liquid droplets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…2 and previous study 13 ), in accordance with earlier reports that Me31B protein level decreases rapidly in the early embryos and at the maternal-to-zygotic transition (MTZ) 17,32 . Alternatively, previous studies reported that certain germ granule RNA-binding proteins can undergo a concentration-and RNA-dependent phase transition from a soluble to viscous state 20,[33][34][35][36][37] , and Me31B, a putative RNA-helicase, may use a similar concentration-dependent mechanism to aggregate into structures like the germ granule RNPs. post-transcriptional regulation 24,26,31,38,39 , we hypothesize that they could have influenced the Me31B expression by regulating the stability of me31B mRNA.…”
Section: Me31b's Aggregation Into the Germ Granules And Me31b Proteinmentioning
confidence: 99%
“…2 and previous study 13 ), in accordance with earlier reports that Me31B protein level decreases rapidly in the early embryos and at the maternal-to-zygotic transition (MTZ) 17,32 . Alternatively, previous studies reported that certain germ granule RNA-binding proteins can undergo a concentration-and RNA-dependent phase transition from a soluble to viscous state 20,[33][34][35][36][37] , and Me31B, a putative RNA-helicase, may use a similar concentration-dependent mechanism to aggregate into structures like the germ granule RNPs. post-transcriptional regulation 24,26,31,38,39 , we hypothesize that they could have influenced the Me31B expression by regulating the stability of me31B mRNA.…”
Section: Me31b's Aggregation Into the Germ Granules And Me31b Proteinmentioning
confidence: 99%
“…(11,12). The functions of RBPs varies and can include translational control, localization, stability, and modifications of RNAs (11,12). Several studies have shown that the conserved germline RBPs Dazl (deleted in azoospermia like), Vasa/Ddx4 (DEAD-box RNA helicase protein 4), Nanos2, and Nanos3 are necessary for germline stem cell establishment or maintenance in zebrafish (8,66,(80)(81)(82).…”
Section: Rna-binding Proteins and Germline Maintenance In Zebrafishmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 22, 2022. ; https://doi.org/10.1101/2022.12.21.521539 doi: bioRxiv preprint Post-transcriptional RNA regulation is critical for many aspects of spermatogenesis. RNA binding proteins (RBPs) form ribonucleoprotein complexes which are important for posttranscriptional regulation of RNAs such as translational control, RNA stability, RNA biogenesis, and modifications of RNAs (11). During spermatogenesis, RBPs play critical roles in all stages of spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…If this is true, we might expect biomolecular condensates formed through phase separation to be ubiquitous in plants, a conclusion we believe is supported by considering extant observations in a new light. Kalinina et al, 2018) nuclear speckles concentrates RNA metabolism factors involved (reviewed in Spector and Lamond, 2011) cajal bodies mRNA metabolism and snRNP biogenesis (reviewed in Ohtani, 2017) DNA damage foci concentrates DNA response proteins (reviewed in Rothkamm et al, 2015) P photobodies concentrates light signaling proteins (reviewed in Ronald and Davis, 2019) dicing bodies miRNA processing (reviewed in Liu et al, 2012) A paraspeckles gene expression regulation by sequestering RNA or proteins (reviewed in Fox et al, 2018) histone locus bodies processing histone pre-mRNAs (reviewed in Nizami et al 2010) PcG body repression of genes related to development (reviewed in Pirrotta and Li, 2012) PML body genome integrity preservation during DNA synthesis (reviewed in Li et al, 2020) nuclear gem SMN complex component localization (reviewed in Gubitz et al, 2004) Cytoplasm P, A processing body mRNA decay and suppression of translation (reviewed in Luo et al, 2018) stress granule translation suppression during stress responses (reviewed in Protter and Parker, 2016) A U body assembly and storage of snRNPs (reviewed in Moser and Fritzler, 2010) germ granule regulation of mRNA translation during germ cell development (reviewed in Trcek and Lehmann, 2017) balbiani body elimination of dysfunctional mitochondria from germline cells (reviewed in Bilinski et al, 2017) and to preserve mitochondria during oocyte dormancy (Boke et al, 2016) RNA transport granule involved in long-range transport of mRNA molecules in axons (reviewed in Pushpalatha and Besse, 2019) Abbreviations are as follows: P, plants; A, Animals. The lack of demonstration of a condensate in either plants or animals does not mean that the condensate does not exist in plants or animals, but rather that we found no evidence demonstrating its existence at the time of this writing.…”
Section: Conserved Condensate Cellular Bodies In Plantsmentioning
confidence: 99%